Wide-field Ca2+ imaging reveals visually evoked activity in the retrosplenial area - Murakami, Tomonari; Yoshida, Takashi; Matsui, Teppei; Ohki, Kenichi (Frontiers in Molecular Neuroscience, 2015)
Due to recent advances of genetic manipulation, mouse brain has become a useful model for studying brain function, which demands whole brain functional mapping techniques in the mouse brain. In the present study, to finely map visual responsive areas in the mouse brain, we combined high-resolution wide-field optical imaging with transgenic mice containing the genetically encoded Ca2+ indicator, GCaMP3. With the high signal amplitude of GCaMP3 expressing in excitatory neurons, this system allowed neural activity to be observed with relatively fine spatial resolution and cell-type specificity. To evaluate this system, we examined whether non-visual areas exhibited a visual response over the entire surface of the mouse hemisphere. We found that two association areas, the retrosplenial area (RS) and secondary motor / anterior cingulate area (M2/AC), were significantly responsive to drifting gratings. Examination using gratings with distinct spatiotemporal frequency parameters revealed that the RS strongly responded to high-spatial and low-temporal frequency gratings. The M2/AC exhibited a response property similar to that of the RS, though it was not statistically significant. Finally, we performed cellular imaging using two-photon microscopy to examine orientation and direction selectivity of individual neurons, and found that a minority of neurons in the RS clearly showed visual responses sharply selective for orientation and direction. These results suggest that neurons in RS encode visual information of fine spatial details in images. Thus, the present study shows the usefulness of the functional mapping method using a combination of wide-field and two-photon Ca2+ imaging, which allows for whole brain mapping with high spatiotemporal resolution and cell-type specificity.